2017
DOI: 10.1002/ana.25023
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient sleep: Enhanced risk‐seeking relates to low local sleep intensity

Abstract: This study provides, for the first time, evidence that insufficient sleep restoration over circumscribed cortical areas leads to aberrant behavior. In chronically sleep restricted subjects, low slow-wave sleep intensity over the right prefrontal cortex-which has been shown to be linked to risk behavior-may lead to increased and subjectively unnoticed risk-seeking. Ann Neurol 2017;82:409-418.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 41 publications
2
25
1
1
Order By: Relevance
“…Subjects who are chronically sleep-restricted may exhibit increased risk-taking behavior, or subjectively may show deficiencies in reasoning that result from seeking premature conclusions without considering all aspects of a problem. This type of impulsivity may manifest also as increased but unnoticed risk-seeking [35]. Insufficient sleep that occurs in children in the preschool and early school years is associated with poorer mother- and teacher-reported neurobehavioral processes, which particularly manifest in mid-childhood [36].…”
Section: Results: Manifestations Of Insufficient Sleepmentioning
confidence: 99%
“…Subjects who are chronically sleep-restricted may exhibit increased risk-taking behavior, or subjectively may show deficiencies in reasoning that result from seeking premature conclusions without considering all aspects of a problem. This type of impulsivity may manifest also as increased but unnoticed risk-seeking [35]. Insufficient sleep that occurs in children in the preschool and early school years is associated with poorer mother- and teacher-reported neurobehavioral processes, which particularly manifest in mid-childhood [36].…”
Section: Results: Manifestations Of Insufficient Sleepmentioning
confidence: 99%
“…[27][28][29] However, other evidence indicated that risky decision-making did not affect by sleep loss robustly. [39][40][41][42] These inconsistent findings may indicate that risk-seeking is not strongly impaired by sleep deprivation and helps to explain why the change in risk-seeking did not correlate with differences in cooperation rates in the PD and CD tasks between normal sleep and sleep deprivation. Second, numerous studies have indicated that sleep deprivation decreases objective alertness and dramatically enhances subjective sleepiness.…”
Section: Discussionmentioning
confidence: 98%
“…Future studies should also include risky decision-making as a cognitive function that relates to the Monday effect. Cognitive failure has been shown to relate risk-bearing behavior in sports [14], and recently, a withinperson study across seven consecutive nights with restricted sleep showed an increase in financial risk-taking [40].…”
Section: Discussionmentioning
confidence: 99%